The Role of the Village Government as a Facilitator in Records (Dynamic Archives) Management (Case Study in Paseban Village, Kencong District, Jember Regency) - Andika Hijrah Prasetyo; Anita Tri Widiyawati (Public Inspiration : Jurnal Administrasi Publik, 2022)
This research uses a case study with a qualitative approach. This study aimed to analyze the role of the Paseban Village Government as a facilitator in managing dynamic archives owned by the village government. As a facilitator, the village government plays a role in creating conducive conditions for the implementation of record management. This has been done even though it is not optimal. Concerning record management, it consists of 1) sorting letters, 2) opening the cover, 3) issuing letters from inside the envelope, 4) examining letters, 5) reading letters, 6) delivering letters (internally), 7) recording letters, and 8) storage of letters related to the Management of incoming mail and procedures for managing incoming letters, there is no SOP. There are four main activities: 1) drafting, 2) approval of letter concepts, 3) typing of letter concepts, and 4) letter delivery. There are also steps for managing outgoing mail, which include: 1) receiving a dictation or written concept from the leadership, 2) drafting a letter, 3) recording the outgoing registration book, 4) typing the letter in its final form, 5) asking for the leadership's signature, 6) checking the mail to be sent, and 7) distributing the mail. However, there is no SOP in the Management of outgoing letters and steps for managing outgoing letters. The criteria for the selection of archival equipment have been carried out. Borrowing archives is no precise loan circulation data because they do not have procedures and do not use archive borrowing books. In addition, there are no restrictions on borrowing archives and determining the period for borrowing archives, so the archive is vulnerable to lose. Record inventory and archive retention at the Paseban Village Office have never been carried out.